Autonomy Oriented Computing From Problem Solving to Complex Systems Modeling - Liu, Jiming; Jin, Xiaolong; Tsui, Kwok Ching; SpringerLink (Online service) (Boston, MA : Springer US, 2005)
Autonomy Oriented Computing explores the important theoretical and practical issues in AOC, by analyzing methodologies and presenting experimental case studies. The book serves as a comprehensive reference source for researchers, scientists, engineers, and professionals in all fields concerned with this promising new development in computer science. It can also be used as a main or supplementary text in graduate and undergraduate programs across a broad range of computer-related disciplines, including Robotics and Automation, Amorphous Computing, Image Processing and Computer Vision, Programming Paradigms, Computational Biology, and many others. The first part of the book, Fundamentals, describes the basic concepts and characteristics of an AOC system, and then it enumerates the critical design and engineering issues faced in AOC system development. The second part of the book, AOC in Depth, provides a detailed analysis of methodologies and case studies to evaluate the use of AOC in problem solving and complex system modeling. The final chapter reviews the essential features of the AOC paradigm and outlines a number of possibilities for future research and development. Numerous illustrative examples, experimental case studies, and exercises at the end of each chapter of Autonomy Oriented Computing help particularize and consolidate the methodologies and theories as they are presented.
Fundamentals -- From Autonomy to AOC -- AOC at a Glance -- Design and Engineering Issues -- A Formal Framework of AOC -- AOC in Depth -- AOC in Constraint Satisfaction -- AOC in Complex Systems Modeling -- AOC in Optimization -- Challenges and Opportunities.
Keywords: Mathematics; Software engineering; Computers; Artificial intelligence; Computer simulation; System theory; Mathematics; Systems Theory, Control; Artificial Intelligence (incl. Robotics).; Computing Methodologies; Theory of Computation; Software Engineering/Programming and Operating Systems; Simulation and Modeling; Electronic books